2013
DOI: 10.1017/s0967199413000403
|View full text |Cite
|
Sign up to set email alerts
|

Embryological, clinical and ultrastructural study of human oocytes presenting indented zona pellucida

Abstract: Human oocyte dysmorphisms attain a large proportion of retrieved oocytes from assisted reproductive technology (ART) treatment cycles. Extracytoplasmic defects involve abnormal morphology of the zona pellucida (ZP), perivitelline space and first polar body. The aim of the present study was to describe a novel dysmorphism affecting the ZP, indented ZP. We also evaluated the clinical, embryological and ultrastructural features of these cases. We evaluated all ART treatment cycles during 7 consecutive years and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 53 publications
2
24
0
1
Order By: Relevance
“…Extracytoplasmic defects include abnormal morphology of the ZP, the PVS, and first PB. Morphological abnormalities of the ZP include a thick, indented, or dark ZP, and can emerge differently in different IVF cycles with the same woman [ 16 28 29 ]. This type of oocyte presents with a total or partial absence of the PVS, an absence of resistance to ZP and oolemma penetration during ICSI, and low ooplasm viscosity during aspiration [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extracytoplasmic defects include abnormal morphology of the ZP, the PVS, and first PB. Morphological abnormalities of the ZP include a thick, indented, or dark ZP, and can emerge differently in different IVF cycles with the same woman [ 16 28 29 ]. This type of oocyte presents with a total or partial absence of the PVS, an absence of resistance to ZP and oolemma penetration during ICSI, and low ooplasm viscosity during aspiration [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy rates from oocytes with specific single abnormalities are difficult to assess because a typical embryo transfer includes mixed embryos generated from normal and dysmorphic oocytes. Nonetheless, a poor pregnancy rate has been reported in oocytes with cytoplasmic granularity [ 14 ], cytoplasmic inclusions [ 8 9 10 14 ], an indented ZP [ 16 ], oval shape [ 30 31 ], a dark ZP [ 11 ], and an abnormal ZP [ 16 ], compared with those without such anomalies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mei Li et al found that the immaturity rate is significantly higher in the abnormal ZP group compared with controls [ 18 ]. Recently, Sousa et al also showed oocytes with indented ZP appear to have only a 42% maturity rate, versus 81.2% for normal oocytes [ 27 ]. It appears that oocytes fail to reach the MII stage because of 4 main reasons: (1) genetic defects, (2) abnormal meiotic recombination, (3) abnormal microfilament action, and (4) failure to produce key cell cycle regulating factors [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…cytoplasmic and nuclear maturity [4][5][6][7][8]. Therefore, numerous factors have been referred as relevant for oocyte competence such as zona pellucida (ZP) morphology [9][10][11][12]; polar body morphology, and chromosome constitution [13][14][15][16][17][18]; metaphase spindle [19][20][21]; chromosome constitution [1,2,7,22]; oocyte DNA damage and repair [22]; cytoplasmic viscosity and resistance to membrane penetration during intracytoplasmic sperm injection (ICSI) [7,23,24]; oocyte shape [7,25,26]; mitochondria aggregation patterns [27,28]; diverse extracytoplasmic and intracytoplasmic inclusions [5][6][7][8]; and abnormal expressed genes [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%